Assessment of Farm-Level Practices of Disease and Pest Management in the Banana Zone of Nawalparasi West district, Nepal - Ghimire, Sudip; Regmi, Anmol (Newinera Publisher, 2024)
Banana (Musa paradisiaca) is a vital fruit crop in Nepal, especially in the Nawalparasi West district, where it can produce and generate income. However, banana farming faces many problems such as diseases and pests that reduce crop yield and quality. This research aimed to assess the state of pest control techniques and banana diseases, providing insights and recommendations for their improvement. A total of 125 banana farmers were selected and the data were analyzed using Microsoft Excel and the Statistical Package for the Social Sciences (SPSS). The findings revealed that the banana leaf and fruit scarring beetle emerged as a particularly troublesome pest (severity index: 0.93), closely followed by the banana aphid (0.67), banana stem weevil (0.51), mealy bug (0.46), and banana rhizome stem borer (0.34). Similarly, diseases such as sigatoka leaf spot exhibited the highest severity (0.76), followed by anthracnose (0.59), bunchy top virus (0.52), bacterial wilt (0.51), and panama wilt (0.43). All participants employed diverse pest management practices, including mechanical, cultural, biological, and chemical methods. Notably, 82.4% utilized fungicides and 100% employed cultural methods, with no adoption of biological approaches. In pest management, 31.2% employed mechanical/physical methods, 95% embraced cultural methods, and all the respondents used pesticides. Positive and significant relationships were identified between respondents' education level, training, farming experience, contact with extension agents, and adoption of disease and pest management practices in banana cultivation.